Azithromycin Modulates 3′, 5′-cyclic Diguanylic Acid Signaling in Pseudomonas aeruginosa. Issue 8 (August 2017) - Kimura, Soichiro; Mori, Nobuaki; Kai, Toshihiro; Ishii, Yoshikazu; Yamaguchi, Keizo; Tateda, Kazuhiro
Abstract: Macrolides have been reported to exert a variety of effects on both host immunomodulation and repression of bacterial pathogenicity. In this study, we report that the 3′, 5′-cyclic diguanylic acid (c-di-GMP) signaling system, which regulates virulence in Pseudomonas aeruginosa, is affected by the macrolide azithromycin. Using DNA microarray analysis, we selected a gene encoding PA2567 related to c-di-GMP metabolism that was significantly affected by azithromycin treatment. Expression of the PA2567 gene was significantly repressed by azithromycin in a time- and dose-dependent manner, whereas no difference in PA2567 gene expression was observed in the absence of azithromycin. In-frame deletion of the PA2567 gene affected both virulence factors and the quorum-sensing system, and significantly decreased total bacteria in a mouse pneumonia model compared to the wild-type strain ( P < 0.05). These results suggest that macrolides possess the ability to modulate c-di-GMP intracellular signaling in P. aeruginosa .